2015
DOI: 10.1186/s13049-015-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of spleen injuries: a retrospective study

Abstract: BackgroundHemorrhage after blunt trauma is a major contributor to death after trauma. In the abdomen, an injured spleen is the most frequent cause of major bleeding. Splenectomy is historically the treatment of choice. In 2007, non-operative management (NOM) with splenic artery embolization (SAE) was introduced in our institution. The indication for SAE is hemodynamically stable patients with extravasation of contrast, or grade 3–5 spleen injury according to the Abbreviated Organ Injury Scale 2005, Update 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Utilizing the NTDB, we studied 53,689 patients who sustained high-grade BSI. Several retrospective studies indicate an association between ANGIO and decreased rates of failure of NOM 2,3,[5][6][7][8][9][10][11][12][13][14][15][27][28][29][30] . Further, several centers now advocate ANGIO for all Grade III to V or IV to V BSI [9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing the NTDB, we studied 53,689 patients who sustained high-grade BSI. Several retrospective studies indicate an association between ANGIO and decreased rates of failure of NOM 2,3,[5][6][7][8][9][10][11][12][13][14][15][27][28][29][30] . Further, several centers now advocate ANGIO for all Grade III to V or IV to V BSI [9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Some centers follow selective ANGIO strategies where patients with BSI and a vascular abnormality seen on admission computed tomography (CT) scan are referred for ANGIO [5][6][7][8] . Other centers, based on evidence that CT may not be accurate at detecting vascular abnormalities that require embolization, advocate for the use of ANGIO for all patients with grades III-V or IV-V BSI, depending on the center [9][10][11][12][13][14][15][16] . Utilizing non-selective ANGIO strategies, authors report improvements in the proportion of patients successfully managed with NOM after protocol implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few meta-analyses showed a significant improvement in NOM success following introduction of AG/AE protocols (OR 0.26, 95% CI 0.13–0.53, p < 0.002) [ 54 , 80 – 82 ]. The failure rate without AG/AE is significantly higher than with AG/AE in AAST-OIS grade IV–V injuries (43.7 vs. 17.3%, p = 0.035, and 83.1 vs. 25.0%, p = 0.016, respectively) [ 80 ].…”
Section: Adult Patientsmentioning
confidence: 99%
“…45 Angiography and embolisation were recommended as an adjunct to nonoperative management for all grade III to grade V injuries. 46,47 However, splenic artery embolisation is associated with various complications (Table 3). [48][49][50][51][52][53][54] One study has shown no significant difference between embolisation and observation alone with regard to successful treatment in patients with blunt splenic trauma.…”
Section: Splenic Artery Embolisationmentioning
confidence: 99%